2016
DOI: 10.11138/mltj/2016.6.1.035
|View full text |Cite
|
Sign up to set email alerts
|

Initial treatment of complete rotator cuff tear and transition to surgical treatment: systematic review of the evidence

Abstract: SummaryBackground: rotator cuff tear affects many people. Natural history, and evidence for non-operative treatment remains limited. Our objective is to assess evidence available for the efficacy and morbidity of commonly used systemic medications, physiotherapy, and injections alongside evaluating any negative long-term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…There were 2,249 primary arthroscopic RCRs performed in patients who have failed conservative therapy between 2010 and 2016 at our institution 11 . A total of 10 patients developed deep shoulder infections after arthroscopic RCR.…”
Section: Resultsmentioning
confidence: 99%
“…There were 2,249 primary arthroscopic RCRs performed in patients who have failed conservative therapy between 2010 and 2016 at our institution 11 . A total of 10 patients developed deep shoulder infections after arthroscopic RCR.…”
Section: Resultsmentioning
confidence: 99%
“…En otra revisión sistemática realizada por Verborgt y col., 10 donde incluyeron 11 estudios que cumplían la metodología exigida por los autores, observaron que no existía evidencia tipo I categórica en indicar cirugía en roturas completas, describiendo que el tamaño de la rotura y síntomas iniciales no se correlacionaban con dolor, función y resultado final. Esos estudios analizan grupos de edad avanzados, y carecen de descripciones morfológicas del tipo de roturas, no quedando claro qué grupo de roturas completas pueden presentar ese tipo de resultados.…”
Section: Consideración #4: Balance De Coplas Musculares Y Fuerzaunclassified
“…An ultrasound screening study revealed that the prevalence of RC tears was 20.47% among 1366 shoulders with or without clinical symptoms, and the prevalence increased with age 7. Initially, RC tears can be treated using conventional methods such as exercise or injections 8…”
Section: Introductionmentioning
confidence: 99%